Soft‐output space‐time block coded spatial modulation. Issue 16 (1st November 2014) - Govender, Rasigan; Pillay, Narushan; Xu, HongJun
Abstract : Space‐time block coded spatial modulation (STBC‐SM) is a recently proposed multiple‐input–multiple‐output transmission scheme, which combines spatial modulation (SM) and Alamouti's space‐time block code (STBC) in such a manner so as to retain the primary advantages of SM and STBC, while avoiding their drawbacks, resulting in an improved system error performance. In this study, the authors propose a soft‐output maximum‐likelihood (ML) detector (SOMLD) and a soft‐output low‐complexity near‐ML detector (SOLCD) for STBC‐SM transmission. Monte‐Carlo simulations demonstrate that the error performance of the proposed schemes are able to closely match that of the hard decision ML detector for uncoded channel conditions, while significant improvement in error performance is demonstrated for coded systems. Furthermore, compared with SOMLD, SOLCD imposes a significantly lower computational complexity, while achieving near‐ML error performance.